A novel implementation of knee joint monitoring device using step index optical fibre and linear array photodiode sensor - G. M., Salim; Mohd Anwar, Zawawi (IOP Publishing, 2020)
Knee monitoring is one of the common injuries suffered by people who are active in extreme sports. Traditional ways to identify these problems are based on background study of the patient, physical examination, and sometimes with the use of x-rays and MRIs. The use of x-rays and MRIs for repetitive use is not preferably suggested by physicians due to the high cost and other associated side-effect related to exposure to radiation. Due to these factors, an alternative device based on optical fibre sensor is proposed in this study. The proposed knee monitoring sensor is based on the use on step index type plastic optical fibre and linear array photodiode sensor. Based on the mathematical estimation and initial sensor measurement, this sensor is able to perform full range of motion between 0 to 155 degrees. The accuracy and resolution of this sensor is 1.0 degree and 0.5 degree, respectively. The aim of this study is to determine the current performance of the device before further improvement could be proposed.